Determinants of Intention to Purchase Ecologically Friendly Products According to the Theory Planned of Behavior (Study on Students of University of Darussalam Gontor) - Rismana, Salsabila; Imari, Iqbal; Ramadhan , Mahendra Utama Cahya (Universitas Al-Qolam Malang, 2025)
The purpose of this research is to analyze the influence of attitudes, subjective norms, and perceived behavioral control with seven intrinsic factors that support the three variables, namely attractiveness, belief, parental support, peer support, family cultural background, self-desire, and self-confidence on students' intention in purchasing ecologically friendly products. The research method used is a quantitative method with data collection techniques using a questionnaire that contains a 5-point Likert scale. The research sample consists of 74 students from Universitas Darussalam Gontor Mantingan Campus 2. The data processing technique in this study was carried out using E-Views 12 software and analyzed using multiple linear regression techniques. The results of this study indicate that based on the analysis of the Theory of Planned Behavior (TPB) regarding students' intention in purchasing ecologically friendly products, there is a significant simultaneous effect. Partially, the six intrinsic factors, namely attractiveness, belief, parental support, peer support, family cultural background, and self-desire does not significantly influence the intention in purchasing ecologically friendly products. On the other hand, only self-confidence as an intrinsic factor of perceived behavioral control significantly influences the intention in purchasing ecologically friendly products.